Latest Electric Vehicle Charging Technology for Smart Grid Application - Tan K.M.; Ramachandaramurthy V.K.; Yong J.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); DC-DC converters; Electric inverters; Electric power system control; Electric vehicles; Power control; Reactive power; Rectifying circuits; Vehicle-to-grid; Voltage control; Voltage regulators; Bidirectional vehicles; Comprehensive assessment; Electric vehicle charging; Power conversion; Power factor corrections; Reactive power compensation; Research and development; Smart grid applications; Electric power transmission networks